Effectiveness of multilevel interventions based on socio-ecological model to decrease sedentary time in children: a systematic review of controlled studies - Cholley-Gomez, Marie; Laujac, Steven; Delpierre, Cyrille; Carayol, Marion (Frontiers in Public Health, 2023)
Objectives Preventive actions of sedentary behavior (SB) based on the socio-ecological model are needed among children and young adolescents. The aim of this systematic review is to ascertain the effectiveness of multilevel interventions (i.e., involving consideration of at least two interventional levels) in reducing sedentary time (ST) in children aged 5–12 years. Methods Adhering to PRISMA guidelines, a systematic literature search was conducted in three databases (PsyInfo, PubMed and ERIC) until July 2021. Results 30 trials met the eligibility criteria and were included. They showed acceptable (< 8, n = 18) and high (≥ 8, n = 12) methodological quality. Among studies targeting 2 (n = 2), 3 (n = 19) and 4 levels (n = 9), 1 (50%), 9 (47%) and 7 (78%) were effective and reported significant reduction of ST, respectively. Conclusion Interventions tend to be more effective when they involve 4 levels, using both agentic and structural strategies (targeting intrinsic determinants, in the organizational environment of the child). Findings underline the relevance of multilevel strategies to reduce ST in children, but also raise issues about operationalization of the socio-ecological perspective. Systematic review registration PROSPERO, identifier: CRD42020209653.